2004
DOI: 10.1002/zaac.200300399
|View full text |Cite
|
Sign up to set email alerts
|

CeAgAs2 — a New Derivative of the HfCuSi2 Type of Structure: Synthesis, Crystal Structure and Magnetic Properties

Abstract: Single crystals of CeAgAs2 have been obtained by chemical transport reactions starting from a pre‐reacted powder sample. The crystal structure was solved using X‐ray diffraction (space group Pmca, No. 57, a = 5.7586(4) Å, b = 5.7852(4) Å, c = 21.066(3) Å, Z = 8) and refined to a residual of R(F) = 0.029 for 46 refined parameters and 1020 reflections. The structure of CeAgAs2 represents a new distorted and ordered variant of the HfCuSi2 type. The characteristic feature of this structure are infinite cis‐trans c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…Similarly, for CeAgAs 2 we corroborate Curie-Weiss character of the magnetic susceptibility above 50 K, reported in Ref. [6]. In contrast to the latter study the sample measured in the present work showed the presence of two features in χ(T), at T N = 6 K and T m = 4.8 K, instead of a single peak at 5.5 K. As displayed in Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, for CeAgAs 2 we corroborate Curie-Weiss character of the magnetic susceptibility above 50 K, reported in Ref. [6]. In contrast to the latter study the sample measured in the present work showed the presence of two features in χ(T), at T N = 6 K and T m = 4.8 K, instead of a single peak at 5.5 K. As displayed in Fig.…”
Section: Resultssupporting
confidence: 92%
“…However, in the case of CeAgAs 2 a few reflections showed some small splitting indicative of orthorhombic distortion, as already reported for this compound in Ref. [6]. No foreign lines were observed in any of the diffraction patterns thus proving single-phase character of the samples used for physical properties studies.…”
Section: Methodsmentioning
confidence: 54%
“…Some ternary rare-earth transition-metal pnictides REM 1-x Pn 2 with SrZnBi 2 -or HfCuSi 2 -type structures are subject to distortion of a square net of Pn atoms [16,[21][22][23][24][25]. This phenomenon is often signalled by abnormally large displacement ellipsoids of the Pn2 site within the parent tetragonal structure.…”
Section: Structure Determinationmentioning
confidence: 99%
“…Indeed, the most prevalent ternary rare-earth transition-metal pnictides are HfCuSi 2 -type phases REM 1-x Pn 2 , where the M site is generally defective if it is occupied by a d-block element other than a monovalent one (i.e., from the Cu triad) [9][10][11]. Among arsenides, the only known representatives thus far are REMAs 2 (M = Cu [12,13], Ag [14][15][16], Au [15]), which are stoichiometric, and REZn 1-x As 2 , which are substoichiometric (REZn 0.67 As 2 ) [17,18]. However, a small Cu excess can be accommodated in lightly stuffed HfCuSi 2 -type phases RECu 1.1 As 2 [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation